Pacts of Molotov Ribentrop: Liebe war es nie - Kanervo , Pirkko (Genocidas ir rezistencija, 2014)
Many Lithuanians and even historians still believe that the fate of Lithuania, Latvia and Estonia was already unconditionally decided after the secret agreements between the Soviet Union and Nazi Germany on 23 August and 28 September 1939. In fact, the course of history might have turned out differently had it not been for the mistaken choice of the Finnish government and the self-isolation and indecision of the US with regard to the European situation in the spring of 1940.